A Novel Method for Simultaneous Monitoring of 2‐MCPD, 3‐MCPD and Glycidyl Esters in Oils and Fats. (26th August 2012) - Ermacora, A.; Hrncirik, K.
Abstract: The availability of a reliable methodology for the quantification of fatty acid esters of monochloropropropanediol (MCPD) and glycidol is essential for understanding the mechanism of formation of these process contaminants and for developing effective mitigation strategies. While several analytical methods for the determination of MCPD esters have already been developed and evaluated, only very few procedures are currently available for the analysis of glycidyl esters. This work presents a new indirect method for the simultaneous quantification of fatty acid esters of 2‐MCPD, 3‐MCPD and glycidol. The method is based on the acid‐catalyzed conversion of glycidyl esters into 3‐monobromopropanediol (3‐MBPD) monoesters which, owing to the structural similarity to MCPD esters, are quantified by using the procedure we previously optimized for the analysis of MCPD esters. The critical step of the method, which is the conversion of glycidyl esters, was optimized by testing different reagent concentrations and varying other condition settings. The novel method showed good repeatability (RSD <2.5 %) and between‐day reproducibility (RSD ≤5 %). The limit of detection was 0.04 mg/kg for bound 2‐MCPD and 3‐MCPD and 0.06 mg/kg for bound glycidol. The trueness of the method was evaluated by the analysis of spiked samples and by interlaboratory comparison.